2018
DOI: 10.1021/acsomega.8b01209
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Sensing of Biotin Using Nafion-Modified Boron-Doped Diamond Electrode

Abstract: Nafion formed on the surface of a boron-doped diamond electrode allows for a chemosensing system for biotin. The modified electrode is capable of oxidizing biotin and offers a detection limit of 5 nM, the average normal level of biotin in blood plasma. The developed method was successfully applied to determine biotin in human plasma samples and a popular health product as two popular models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…A number of studies have been reported on the potential utilization of avidin–biotin interaction in sensing technology. Using various detection methods such as competitive immunoassay, electrochemical, cyclic voltammetry, and immunoaffinity chromatography, detection limits ranging from 2 pM to 84 nM have been reported (Table ). It seems that the present AuNP-GFET biosensor based on the avidin–biotin technology shows the highest sensitivity and quick detection time.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have been reported on the potential utilization of avidin–biotin interaction in sensing technology. Using various detection methods such as competitive immunoassay, electrochemical, cyclic voltammetry, and immunoaffinity chromatography, detection limits ranging from 2 pM to 84 nM have been reported (Table ). It seems that the present AuNP-GFET biosensor based on the avidin–biotin technology shows the highest sensitivity and quick detection time.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, HPLC equipped with a downstream BDD electrode may be used for the separation and sensitive detection of BAK Full Paper homologs, formulated in pharmaceutical preparations [16]. If necessary, the electrode can be coated with Nafion [28], a negatively charged polymer to enhance the selective adsorption of BAK homologs. In this context, the electrode can be deposited with the negatively charged sulfobutylether-beta-cyclodextrin-doped poly(Nacetyltyramine) [29].…”
Section: Discussionmentioning
confidence: 99%
“…To date, a number of studies have reported on the utilization of avidin-biotin interaction in sensing technology [46][47][48][49][50]. The detection limits ranged from 2 pM to 84 nM have been reported using various detection methods such as competitive immunoassay, electrochemical, cyclic voltammetry, and immunoaffinity chromatography as listed in Table 5.1.…”
Section: Comparative Sensitivity and Practical Applicabilitymentioning
confidence: 99%